Seashore baby - Broach, Elise; Doerrfeld, Cori (New York : LB kids, 2010)
Simple text and illustrations with lift-the-flaps describe a baby's fun day at the beach.
Cover title.
On lift-the-flap board pages.
2.1
K-3
Keywords: Beaches -- Juvenile fiction; Infants -- Juvenile fiction; Toy and movable books -- Specimens; Babies -- Fiction; Beaches -- Fiction; Stories in rhyme; Toy and movable books; Beaches -- Fiction; Infants -- Fiction; Stories in rhyme; Toy and movable books